\[ \begin{array}{l}\text { Solve the equation for } y \text {. Write the answer in } y=m x+b \text { form. } \\ y+3=-\frac{1}{3}(x-4)\end{array} \] \( y=\square \) (Use integers or fractions for any numbers in the expression.)
Solución de tutoría real
Responder
Solución
¡Inicia sesión para desbloquear respuestas gratis!
Una plataforma de aprendizaje en la que confían millones de estudiantes y profesores reales.
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To solve the equation for \( y \), start with the original equation: \[ y + 3 = -\frac{1}{3}(x - 4) \] First, distribute the \(-\frac{1}{3}\): \[ y + 3 = -\frac{1}{3}x + \frac{4}{3} \] Next, isolate \( y \) by subtracting 3 from both sides: \[ y = -\frac{1}{3}x + \frac{4}{3} - 3 \] Now, convert 3 to a fraction with a denominator of 3: \[ 3 = \frac{9}{3} \] So, we have: \[ y = -\frac{1}{3}x + \frac{4}{3} - \frac{9}{3} \] Combining the constants gives: \[ y = -\frac{1}{3}x - \frac{5}{3} \] Thus, in slope-intercept form \( y = mx + b \), the solution is: \[ y = -\frac{1}{3}x - \frac{5}{3} \]